A Study of Customer Perception towards Service Quality of Life Insurance Companies in Delhi NCR Region (Global Journal of Management and Business Research, 2014)
Economic performance of insurance companies is the outcome of customer's satisfaction and their perception on service quality of the insurance service provider. The present study has focused on finding customer perception towards service quality as provided by the Life Insurance companies. The primary data has been collected from 139 respondents from Delhi NCR Region. The factor analysis and correlation has been used to find the perception of the customers. The study has found that there are four major factors which influence customer perception of service quality, namely responsiveness and assurance, convenience, tangible and empathy. Only age of the respondents have been found to be significantly related with the customer perception and other demographic factors have no significant impact.
Keywords: life insurance; service quality; customer perception; india